TIP41L, a putative candidate gene conferring both seed size and boll weight, was fine-mapped in an introgression line of Gossypium hirsutum-Gossypium arboreum. (April 2022) - Feng, Liuchun; Su, Qiao; Yue, Haoran; Wang, Liang; Gao, Jianbo; Xing, Liangshuai; Xu, Min; Zhou, Chenhui; Yang, Ying; Zhou, Baoliang
Highlights: A boll-and-seed size QTL, q(BW+SI)-A12-1, was fine-mapped to a 60.09 kb region, including five candidate genes. qRT-PCR and comparative analyses revealed TIP41L was the putative candidate gene conferring boll-and-seed size in cotton. TIP41L gene was diverged after the formation of polyploid cotton and swept during domestication of modern upland cotton. Our results would lay a solid foundation for elucidating the molecular mechanism of cotton boll and seed development. Abstract: QTLs for yield-related traits in tetraploid cotton have been widely mapped, but QTLs introduced from diploid species into tetraploid cotton background remain uninvolved. Here, a stable introgression line with the traits of small boll and seed on Chr. A12, IL197 derived from Gossypium hirsutum (2 n = AADD = 52) × Gossypium arboreum (2 n = AA = 26), was employed to construct the F2 and F3 secondary populations for fine-mapping QTLs of yield-related traits. QTL analysis showed eight QTLs were detected for three traits, boll weight (BW), seed index (SI, one-hundred-seed weight in g), and lint percentage, with 3.94–28.13 % of the phenotypic variance explained. Of them, a stable major QTL, q(BW + SI)-A12-1 controlling both BW and SI and covering the shortest region in Chr. A12, was further narrowed into a 60.09 kb-interval through substitution mapping. Finally, five candidate genes were detected in the interval. The qRT-PCR analysis revealed only TIP41-like family protein ( TIP41L ) kept up-regulated expression and significantly lower in TM-1 than that in IL197 from -1 DPA to 15 DPA during cotton boll rapid developmental stage. Therefore, TIP41L gene is speculated as the most likely candidate gene. Comparative analysis with the other four allotetraploid species showed TIP41L gene was probably diverged after the formation of allotetraploid cotton, which may be selected and swept during domestication of modern upland cotton because small boll and seed are detrimental to fibre yield of cotton. This research would lay a solid foundation for further elucidating the molecular mechanism of cotton boll and seed development.